The silenced text: field experiments on gendered experiences of political participation - Yan, AN; Bernhard, R (Cambridge University Press, 2023)
W ho gets to “speak up” in politics? Whose voices are silenced? We conducted two field experiments to understand how harassment shapes the everyday experiences of politics for men and women in the US today. We randomized the names campaign volunteers used to text supporters reminders to participate in a protest and call their representatives. We find that female-named volunteers receive more offensive, silencing, and withdrawal responses than male-named or ambiguously-named volunteers. However, supporters were also more likely to respond and agree to their asks. These findings help make sense of prior research that finds women are less likely than men to participate in politics, and raise new questions about whether individual women may be perceived as symbolic representatives of women as a group. We conclude by discussing the implications for gender equality and political activism.